Challenges Facing Publicity and Marketing of Nigeria Commercial Theatre in a Depressed Economy - Akpodiete, Hannah Modupe (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2020)
For a commercial theatre to remain in business, it must continually adjust itself economically, socially and politically to its immediate environment. The world is changing so fast that industrialised economist has equally changed drastically. This has necessitated the increase in global competition and liberalisation of markets combined with change in consumer demand, values and priorities. This has forced companies to cut out wasteful and unproductive activities and concentrate on areas of competence to achieve sustainable competitive advantage. Also, the worldwide economic recession has reduced the consumer purchasing power and brought companies face to face with complex cross-cultural issues and competition that necessitates aggressive publicity and marketing for its survival in a depressed economy. Furthermore, to survive this unprecedented turmoil, most organisations especially commercial theatre had to embark on a number of measures including aggressive publicity and marketing, For the theatre industries to survive the 21st century in a depressed economy, it must be responsive to its environment, as well as be creative, built on trust and developed self-knowledge. To achieve this the qualitative research methodology was employed using the Laissez faire Model of economic recovery in recession. The marketing/publicity manager could help the Commercial theatre achieve her corporate vision through allowing the spirit of cooperation and teamwork among all partners within the organization. This paper therefore analyses different methods used by commercial theatre organisations in the current dispensation when the nation is facing a downturn economy and equally suggests new strategies employed by them towards alleviating their economic challenges.